Application of Azospirillum brasilense and Humic Substances Improves the Nursery Quality of Olive Seedlings in Pots - Giovana Ritter; Rodrigo José de Vargas; Daniela Farinelli; Nicola Cinosi; Chiara Traini; Simona Lucia Facchin; Larissa Hiromi Kiahara; Daniel Fernandes da Silva; Silvia Portarena; Fabiola Villa (Horticulturae)
In Brazil due to the establishment of new orchards, olive seedling production is growing strongly, while the use of biostimulants in agriculture has been gaining attention due to their benefits in root formation and nutrient absorption. This study evaluated the use of biostimulants for promoting the growth of 3-month-old rooted olive seedlings in pots and to assess the nursery quality of the seedlings. Rooted cuttings of Arbequina, Maria da Fé, and Ascolano 315 cultivars were treated with Azospirillum brasilense (Az) and humic substances (HS), alone and in combination. Growth parameters, such as height and stem diameter, were measured every month and after 150 days, seedlings per treatment were also analysed for aerial and root fresh and dry biomasses. Arbequina exhibited the highest growth rate with Az and best absolute growth rate with Az + HS treatment. The total dry matter of the olive seedlings, comprising both the aerial and root part, was influenced by both Azospirillum brasilense and humic substances, enhancing nitrogen availability. The three treatments showed their positive effects on aboveground growth and overall plant vigour. Despite increased biomass, treated olive seedlings showed no significant height advantage over controls, suggesting that the effects may appear in later developmental stages.